Skeletal Rearrangements Involving Cyclopropyl- and Alkene-Stabilized Silylium Ions - Long, Peng-Wei; He, Tao; Klare, Hendrik F. T.; Oestreich, Martin (Synlett, 2023)
This Account summarizes the fascinating chemistry of cyclopropyl-stabilized silylium ions, which are readily available from vinylcyclopropanes (VCPs). Depending on the nucleophilic partner, these reactive intermediates undergo direct ring opening or ring expansion to nonclassical alkene-stabilized silylium ions. The latter can also be accessed by gold as well as proton electrophiles from silicon compounds containing unsaturated C–C bonds. All these reaction cascades can be terminated by C–H or C–C as well as Si–O bond formation. From this, a clearer picture of the versatility of these rather complex chemistries emerges.1 Introduction2 Skeletal Rearrangements of Vinylcyclopropanes Involving Cyclopropyl-Stabilized Silylium Ions2.1 Termination by C–H Bond Formation2.2 Termination by C–C Bond Formation3 Related Bond Reorganizations Involving Alkene-Stabilized Silylium Ions3.1 Initiation by Cationic Gold(I) Complexes3.2 Initiation by Brønsted Acids4 Conclusion
Keywords: β-silicon effect; bond reorganization; carbenium ions; ring expansion; silylium ions; skeletal rearrangements; vinylcyclopropanes